Serum Dehydroepiandrosterone sulfate (DHEA-S) level and its potential impact on immune responses and symptom severity after Oxford-AstraZeneca COVID-19 vaccination - Abbasifard, Mitra; Dehghan Banadaki, Maryam; Taghipour Khaje Sharifi, Gholamhossein; Rahnama, Amir; Bagheri-Hosseinabadi, Zahra (International immunopharmacology, 2024)
•No significant difference observed in DHEA-S levels before and after the first and second doses of vaccination.•IL-2 and IFN-γ levels significantly increased in PBMC supernatant two weeks after both initial and booster vaccinations.•Serum IgM levels significantly rose two weeks after the first dose, while IgG levels increased significantly after both the first and second doses.•FRNT50 titer significantly elevated two weeks post both initial and booster doses, indicating heightened neutralizing antibody response.•DHEA-S levels showed no significant correlation with IL-2, IFN-γ, IgM, IgG, and FRNT50 levels before and after vaccinations.•No intense unwanted clinical presentations observed post-vaccination. Dehydroepiandrosterone sulfate (DHEA-S) has been associated with an immunomodulatory function. This study aims to explore the relationship between serum levels of DHEA-S and the immune responses triggered by the Oxford–AstraZeneca COVID-19 vaccine in individuals candidate for vaccination. Serum levels of DHEA-S, cytokine release, antibody production and virus neutralization potential were assessed in 50 male and 50 female subjects before and 2 weeks after vaccination with Oxford–AstraZeneca COVID-19 vaccine. Level of DHEA-S before and 2 weeks after first and second dose of vaccination was not different significantly. Levels of Interleukin (IL)-2 and Interferon (IFN)-γ were significantly higher in the supernatant of peripheral blood mononuclear cells (PBMCs) obtained from subjects 2 weeks after both first and second dose of vaccination compared to before vaccination. Serum levels of IgM 2 weeks after first dose of vaccination was significantly higher compared to before first dose of vaccination. However, serum levels of IgG 2 weeks after first and second dose of vaccination were significantly higher compared to before first and second dose of vaccination. The 50 % focus reduction neutralization test (FRNT50) titer was significantly higher 2 weeks after both first and second dose of vaccination compared to before vaccination. Levels of DHEA-S did not have significant correlation with levels of IL-2, IFN-γ, IgM and IgG, and FRNT50 before and after first and second dose of vaccination. Vaccination did not result in intense unwanted clinical presentations. DHEA-S is not involved in the quality of protective immune response during Oxford-AstraZeneca COVID-19 vaccination.